Analyse Critique de la Reparation du Prejudice de la Contrefacon de Droits d’auteur (African Journal of Law and Politics, 2023)
This contribution highlights the limits of the common civil liability law, which does not allow the prejudice of counterfeiting to be repaired in a satisfactory manner and proposes to consider this right in a particular way when it will come to repair this prejudice. Common law, which remains the foundation of the system, must however be adapted by taking into account the specificities of counterfeiting. For this purpose, in addition to the lost of profit and the losses suffered by the rights holder, the taking into account of the profits made by the infringer, the increase of the compensation to be allocated when this profit is non-existent and finally, the institution of another approach to assessing compensation for counterfeiting will make it possible to improve the damage compensation system and to fight effectively against counterfeiting.